One Health in managing zoonotic diseases - Karani, Maurice K. (International Livestock Research Institute, 2021)
Maurice Karani, veterinarian and epidemiologist at ILRI, discusses the role of One Health in managing zoonotic diseases. This film is part of the ILRI and CGIAR 'Investing in One Health' video series.